(untitled) (Journal of Human Sciences, 2021)
Narratology are no longer captive to the traditional structural view since the end of the twentieth century. New turns in the epistemological fields around them have pushed them to drop The separation wall between text and its contexts, from these turns is the linguistic After the opening of linguistics to the context, the self is presented in the text and linked in situation, the theorists of the narrative did not find it seemed from turning into this openness and being influenced by it. However, this turning point made narratives directed more to discourse than to story, and the narrative is only correct with them. That is why narrative theorists have found in the developments of the humanities and social sciences what complements this deficiency. Looking at the story is no longer limited to events and the extent of change in cases of narrative aid and its stations only. Rather, it is as a representation of an individual human experience that stores the experiences of societies. Accordingly, this research seeks to analyze one of the traditional narratives that represent the most important human experiences, which are the love narratives. The stories of the lovers confuse the verbal with the book, the marginal with the central, and the self with the other. And above all, the historical, literary and religious confusion? What relationship does the news of lovers establish with these discourses, and specifically the Sufi discourse? What relationship does a madman have with the world of love? What is the acquired identity of a madman of love in Sufi discourse? We will try to answer these questions, supplicating the possible-worlds theory approach.